Exploring the Nexus of ESG, Family Firms, and Financial Risk in Indonesia - Parasdya Pandhu Andanawarih; Lalu Yayan Ardiansyah; Yolanda Dhamayanti (LPPM Universitas Pekalongan, 2025)
This study examines the impact of environmental, social, and governance (ESG) performance and family ownership on financial risk. While existing literature offers mixed evidence on how ESG affects financial risk, it remains unclear whether family-owned firms known for their long-term orientation and socioemotional wealth goals, which align closely with ESG principles are better able to mitigate financial risk. To address this gap, we introduce a novel framework that incorporates family ownership into the analysis of the ESG–financial risk relationship, with a particular focus on Indonesian firms. Using a fixed‑effects model, panel regression on 462 firm‑year observations, we find that stronger ESG performance is associated with lower financial risk. However, our investigation results show that family ownership is not correlated with financial risk, while also reinforcing our finding that family ownership unable to moderate the relationship between ESG and financial risk. This finding will help investors and portfolio managers evaluate how ESG, ESG controversies, and ownership structure influence a firm’s financial risk, and will assist them in making better investment decisions.